PENGGUNAAN TEKNIK SNOWBALL THROWING UNTUK MENINGKATKAN KETERAMPILAN MENULIS KALIMAT SEDERHANA BAHASA PRANCIS - Amanda, Alifia Winy (2015)
The phenomenonofstudents' difficultiesin writing in French has been the background of this study. Such difficulty arises because of students' limited vocabulary and grammatical structures (Malgarejo, 2010), and difficulty of getting an idea resulting from a lack of motivation (Muliawati, 2012).This research aims to describe (1) the level of skills to write simple sentences in French before and after conducting Snowball Throwing technique; and (2) the students' responses towards the use of Snowball Throwing technique in learning to write simple sentences in French. The method used in this study is pre-experimental, with one-group pre-testandpost-test design. Instruments used in this research are in the form of literature studies, written tests and questionnaires. Results show that the pre-test score of the students is 5.85 and post-test score of the students is 8.22. The level of significance of a simple sentence writing skills students are known fromt_count. The statistical calculation data shows t-count of 6.34. With a significance level of 5% and with a degree of freedom (db) by 19, the obtained value t-table is 2.09. The result shows thatf >t_(tabel )(6.34> 2.09). This indicated that there are significant differences on the level of skill of writing simple sentences before and after the use of Throwing Snowball techniques.Therefore, it can be concludedthat theSnowballThrowinglearning techniquescan beapplied in teachingFrenchlanguageto writesimple sentences. Thequestionnaire datashow thatall students(100%) statethatSnowballThrowinglearningtechniquescan assistthemin learningto write inFrench. According to half of the number of students (50%), this technique is very interesting to be applied in learning. Keywords: french, simplesentence, writing, snowballthrowing, learningtechniques thitung>ttabel (6,34 > 2,09). Maka dari itu dapat disimpulkan bahwa terdapat perbedaan signifikan dari tingkat keterampilan menulis kalimat sederhana sebelum dan sesudah digunakannya teknik Snowball Throwing. Berdasarkan skala penilaian, pemerolehan nilai rata-rata tersebut dapat dikategorikan baik. Dengan demikian dapat disimpulkan bahwa teknik pembelajaran Snowball Throwing dapat diterapkan dalam pembelajaran menulis kalimat sederhana bahasa Prancis. Adapun data angket menunjukkan bahwa seluruh siswa (100%) mengatakan bahwa teknik pembelajaran Snowball Throwing dapat membantu mereka dalam pembelajaran menulis bahasa Prancis. Teknik inipun menurut setengah dari jumlah siswa (50%), sangat menarik untuk diterapkan dalam pembelajaran. Kata kunci: bahasa prancis, kalimat sederhana, menulis,snowball Throwing, teknik pembelajaran